The future of large, internationally active banks: Does scale define the winners? - Joseph P. Hughes; Loretta J. Mester (Rutgers University, Department of Economics, 2015)
Our research as well as that by other authors has found scale economies at all sizes of banks and the largest scale economies at the largest banks - that is, larger banks are able to provide products at lower average cost than smaller banks. While the earlier literature found that scale economies are exhausted beyond a modest size - no larger than 100 billion and usually much smaller - a number of recent studies have found scale economies beyond this point, in fact, economies that increase with size. Based on a model that appropriately accounts for endogenous risk-taking and controls for any cost-of-funding advantages conferred on large banks, we find that technological factors, not advantages in funding costs, account for their scale economies. The literature does not indicate whether these benefits of larger size outweigh the potential costs in terms of systemic risk that large scale may impose on the financial system. However, if public policy considerations imply that society would be better off with smaller financial institutions, restrictions that limit the size of financial institutions, if effective, may put large banks at a competitive disadvantage in global markets where competitors are not similarly constrained. Moreover, size restrictions may not be effective since they work against market forces and create incentives for firms to avoid them. Avoiding the restrictions could thereby push risk-taking outside of the more regulated financial sector without necessarily reducing systemic risk. If such limits were imposed, intensive monitoring for such risks would be required. These factors need to be considered when evaluating policies concerning financial institution scale.
Keywords: G21; G28; 330; banking; efficiency; scale economies; regulation